Upper limb exercise training and activities of daily living in patients with COPD: a systematic review of randomized controlled trials - Karagiannis,Christos (2020)
ABSTRACT Objective: To investigate the efficacy of upper limb exercise training (ULExT) in improving the performance of activities of daily living (ADL) that involve the upper limbs (UL) in patients with COPD. Methods: The Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines were used in this systematic review. PubMed and EBSCOhost databases were searched to identify randomized controlled trials involving adults with COPD who underwent ULExT, compared with those who underwent other types of exercise or no exercise, in order to assess the performance of ADL that involve the UL. The methodological quality of the selected studies was assessed using the Physiotherapy Evidence Database scale. Results: Five studies, with a total sample of 173 subjects, met the inclusion criteria. The results of the selected studies showed that ULExT is safe and can significantly improve the performance of ADL that involve the UL in patients with COPD. However, there were inconsistencies in the results, especially regarding the perception of symptoms during ADL. The small number of studies included and their methodological quality do not allow for firm conclusions. Conclusions: The findings of this review revealed that ULExT is a safe therapeutic approach and can improve the performance of ADL that involve the UL in patients with COPD, but the results are unclear. Further investigation through well-designed randomized trials is warranted to determine the effectiveness of ULExT in improving the performance of ADL that involve the UL in patients with COPD.